PENGARUH LINGKUNGAN KERJA DAN BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN PADA TAMAN SIMALEM RESORT - Maludin Panjaitan; Selamat Siregar; Novita Surtana Rouli Sianipar (Universitas Methodist Indonesia, 2021)
The purpose of this study was to determine and analyze the influence of the work environment and corporate culture on employee performance at Taman Simalem Resort. The number of samples in this study were 70 people. The results showed that partially there was a positive and significant influence between work environment on employee performance, corporate culture partially had a positive and insignificant effect on employee performance and simultaneously work environment and corporate culture had a positive and insignificant effect on employee performance at Taman Simalem Resort with a coefficient of determination R2 = 0.025, which means that the work environment and corporate culture have an effect on the performance of employees at Taman Simalem Resort amounting to 2.5%, while the remaining 97.5% is influenced by other variables not researched.